Influences of motivation and grit on students' self-regulated learning and English learning achievement: A comparison between male and female students. (June 2023) - Guo, Wenjuan; Bai, Barry; Zang, Fengxiang; Wang, Tianqi; Song, Huan
Abstract: This study investigated the influences of motivation and grit on students' self-regulated learning (SRL) and achievement in English as a foreign language (EFL), and compared such influences between male and female students. A total of 723 primary students in Hong Kong participated in this study. Results of MANOVAs indicated that there were generally no gender differences in students' motivation, grit and SRL strategy use in EFL, except for growth mindset, but female students had a better level in English learning achievement than male students. Results of two-group structural equation modeling (SEM) suggested that grit was the greatest predictor of SRL strategy use for both male and female students, and self-efficacy predicted all students' critical thinking and English learning results. Unexpectedly, intrinsic motivation only predicted male students' English learning results, and growth mindset only predicted male students' English learning results and female students' critical thinking. Implications for future research and EFL teachers to promote male and female students' SRL strategy use and English learning are discussed.